Large capacity multi-float configurations for the wave energy converter M4 using a time-domain linear diffraction model. (October 2017) - Stansby, Peter; Carpintero Moreno, Efrain; Stallard, Tim
Highlights: A time-domain linear diffraction model for the multi-float multi-mode wave energy converter M4 has been presented. The model for a three float configuration closely approximates results of laboratory experiments. The model for the device has been extended up to eight floats with a single bow float and multiple mid and stern floats. Energy capture has been increased markedly by increasing the number of floats. Capacity and cost of electricity for various sites has been shown to be similar to offshore wind. Abstract: The moored three-float line absorber WEC M4 has been developed to optimise power capture through experiments and linear diffraction modelling. With the progression down wave from small to medium to large floats, the device heads naturally into the wave direction. The bow and mid floats are rigidly connected by a beam and a beam from the stern float is connected to the hinge point above the mid float for power take off (PTO). Increasing the bow to mid float spacing to be more than 50% greater than the mid to stern float spacing has been found to improve power capture. To increase power capture further and potentially reduce electricity generation cost the number of mid floats and stern floats is increased while maintaining a single bow float for mooring connection. The bow and mid floats still form a rigid body while the stern floats may respond independently. A time domain linear diffraction model based on Cummins method has been applied to configurations of 121, 123, 132, 133, and 134 floats where the numbers indicate the number of floats: bow, mid, stern. This shows how power capture is increased while response remains similar. We only consider uni-directional (long-crested) waves with narrow band width typical of swell. By considering scatter diagrams for various offshore sites capacities may range from 3.7 MW to 17.3 MW for the eight float system with a capacity factor of 1/3 while the cost of electricity assuming capital cost to be a fixed multiple of steel cost is reduced from that for the three-float system.